2003
DOI: 10.1002/macp.200290071
|View full text |Cite
|
Sign up to set email alerts
|

Combining ATRP of Methacrylates and ROP of L,L‐Dilactide and ε‐Caprolactone

Abstract: Coupling atom transfer radical polymerization (ATRP) and coordination‐insertion ring‐opening polymerization (ROP) provided a controlled two‐step access to polymethacrylate‐graft‐polyaliphatic ester graft copolymers. In the first step, copolymerization of methyl methacrylate (MMA) and 2‐hydroxyethyl methacrylate (HEMA) was carried out at 80 °C at high MMA concentration by using ethyl 2‐bromoisobutyrate and [NiBr2(PPh3)2] as initiator and catalyst, respectively. Kinetic and molar masses measurements, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 26 publications
0
47
0
Order By: Relevance
“…Meanwhile, ATRP has been proved to be efficient to synthesize polymer with desired macromolecular architectures [33][34][35][36]. Therefore, it is very interesting to combine ROP and ATRP to synthesize PCL-based copolymers with controlled length, composition, and architecture of polymer chains [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, ATRP has been proved to be efficient to synthesize polymer with desired macromolecular architectures [33][34][35][36]. Therefore, it is very interesting to combine ROP and ATRP to synthesize PCL-based copolymers with controlled length, composition, and architecture of polymer chains [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Using this methodology, graft copoly(ester-vinyl alcohol) [27,[141][142][143][144][145], copoly(ester-amine) [146], copoly(ester-acrylate) [42,147] and polyester grafts on polysaccharides [148][149][150][151][152] have been obtained.…”
Section: Graft Polymers (Polyester Chains Grafted From/onto Other Polmentioning
confidence: 99%
“…Duda and Dubois used the "grafting from" technique for the synthesis of graft copolymers using MMA/HEMA copolymer as a backbone with pendant initiating -OH groups for ε-caprolactone and lactide polymerization (toluene as a solvent, 80°C, Sn(Oct) 2 as a catalyst) [147]. …”
Section: Scheme 19mentioning
confidence: 99%
“…Recently, many studies have been reported in the literature about the synthesis of macromolecules with various compositions (homopolymers, random, periodic, block, graft and gradient copolymers) and novel topologies (linear, star, comb, branched, hyper branched, networks, brushes etc.) using CRP techniques [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. It is observed that the significant improvement in block and graft copolymer synthesis has become with development of controlled/living radical polymerization (CRP) techniques.…”
Section: Introductionmentioning
confidence: 99%